In vitro comparison of force losses over time of orthodontic nickel-titanium closed springs, elastomeric chains, and active tie-backs - Emine Aydın; Nurhat Özkalaycı; Orhan Çiçek (Gazi University, 2024)
OBJECTIVE: This study aims to compare the force losses of nickel-titanium closed springs, elastomeric chains, and active tie-backs over time in an in vitro environment containing artificial saliva. MATERIALS AND METHODS: In the study, elastomeric chains, nickel-titanium closed springs, and active tie-backs from 3 different brands were divided into 9 groups. The percentages of force loss in the samples over time were compared in the in vitro environment containing artificial saliva. Force values were measured and recorded at initial activation, 1st hour, 24th hour, 7th day, 21st day, and 28th day. Statistical analysis of the data were performed with Kolmogorov-Smirnov, Kruskal Wallis, Mann-Whitney U, and Wilcoxon tests. The significance value was considered as p<0.05. RESULTS: The highest and lowest forces at the initial activation hour were measured in elastomeric chains and nickel-titanium closed springs, respectively (p<0.05). There was no significant difference between elastomeric chains, nickel-titanium closed springs, and active tie-backs in the measurements performed at the 24th hour (p>0.05). Although significant force losses were measured in all groups on the 28th day, active tie-backs lost significantly less force than elastomeric chains, regardless of brand. On the 28th day, the lowest and highest forces were measured in elastomeric chains and nickel-titanium closed springs, respectively (p<0.05). CONCLUSIONS: Among the orthodontic space closure mechanics, nickel-titanium closed springs were the most stable; however, active tie-backs produced a more stable force than elastomeric chains, so the type of force element used was the main indicator of the force loss level.